A sazonalidade e a disponibilidade de recursos afetam a diversidade de borboletas frug?voras (Nymphalidae) ao longo do tempo e da estratifica??o vertical? - Nascimento, Bianca Santana Dias (2024)
Vertical stratification in forests limits the spatial distribution of species, leading to distinct species composition between strata. Additionally, climatic seasonality is one of the main determinants of the growth cycles and production of leaves, flowers and fruits by plants, which directly interferes with the temporal distribution of insect communities, including butterflies. The objective of this study was to determine the effects of vertical stratification (canopy vs understory) and temporal variation on the frugivorous butterfly community, and their relationships with climatic factors and food resource availability. The study was carried out in Serra da Jacobina, located in the Center-North of Bahia, in the region of the municipality of Ant?nio Gon?alves (10?35?51? S and 40?20?42? W). The mountain range is 250 km long and is part of the extreme northern portion of the Espinha?o Range, inserted in the Caatinga biome. Sampling was carried out in a seasonally dry tropical forest located in the portion of the mountainous complex known as Serra da Bananeira. 20 plots (25m x 4m) were sampled over 12 months. Two traps (Van Someren Rydon) were installed in the center of each plot, one in the canopy (? 6m) and the other in the understory (1m), removed after 48 hours. Climatic variables (temperature, luminosity, air humidity and precipitation), resource availability (density of plants with zoochoric fruits and fruiting intensity) and canopy coverage were measured monthly. 52 species were recorded, the Biblidinae subfamily, with 16 species and the Satyrini tribe, with 25 species, represent more than 70% of the individuals in the community. The species Hamadryas februa (Biblidinae) was the most frequent in the study and dominant in the understory. In the canopy, the species Biblis hyperia nectanabis (Biblidinae) was the most common. A vertical partition of the niche was observed, in which species composition differed between understory and canopy, probably due to microclimatic variation between strata. A greater abundance of butterflies was recorded in the understory, however, species richness did not differ between strata. There was a change in the richness, abundance and distribution of fruit butterflies (Nymphalidae) over time. The greatest diversity of butterflies was recorded in hot and dry periods, and there was a ?time-lag? of two months after the peak rainfall of the rainy season. The subfamilies also varied in abundance according to temporal seasonality, and appear to avoid competition for habitat, with life cycles and reproduction occurring at different periods in time. The community's high diversity and differences in vertical and temporal structure show the importance of considering these variables in conservation surveys.